Sustainability reporting after the Costa Concordia disaster: a multi-theory study on legitimacy, impression management and image restoration. Issue 8 (10th July 2020) - Corazza, Laura; Truant, Elisa; Scagnelli, Simone Domenico; Mio, Chiara
Abstract : Purpose: Can sustainability disclosures be a tool for executing image restoration strategies after corporate manslaughter? This is the question explored in this study of Costa Crociere's sustainability reports after the Concordia disaster. Design/methodology/approach: Merging traditional textual content analysis with visual analysis and supported by machine learning tools, this is a predominantly qualitative study framed by legitimacy theory, image restoration theory and impression management. Findings: Costa Crociere's voluntary sustainability reporting is strongly influenced by a mix of text and visual signals that distract readers' attention from the disaster. A "nothing really happened" communication strategy pervades the disclosures, with the only rational motivation being to change perceptions and erase memories of this tragic and avoidable event. Research limitations/implications: Although the analysis covered multiple sources of corporate information, media coverage was not one of them. A more in-depth exploration of sustainability reporting in the cruise industry, including evidence of similar cases, to test impression management theory would be a worthwhile avenue for future research. Social implications: While Costa Crociere technically followed the customary guidelines of disclosing human resource impacts, there was almost no acknowledgement of the people involved in the accident. Costa Concierevastly understated their responsibility for the accident, did not apologize, and conveyed very little remorse. The majority of disclosures centred on disaster recovery management. Originality/value: The authors discuss why and how a company can overcome a legitimacy threat by completely freezing its voluntary sustainability reporting, and the authors show how a company can restore its image by minimizing specific aspects of an accident and shifting attention from the human victims to corporate operations. Incorporating image recognition driven by AI models and combining the results with narrative disclosures contributes an innovative and original analysis technique to the field of impression management. In addition, this research also contributes to our knowledge on the cruise industry – a sector currently under scrutiny for its ethical, social and environmental practices.